Emerging Africa how 17 countries are leading the way - Radelet, Steven C. (Baltimore Center for Global Development, 2010)
Emerging Africa describes the too-often-overlooked positive changes that have taken place in much of Africa since the mid-1990s. In 17 countries, five fundamental and sustained breakthroughs are making old assumptions increasingly untenable
Includes bibliographical references
Keywords: Africa-Economic conditions-1960-